Maximum Pressure Controller for Stabilizing Queues in Signalized Arterial Networks. Issue 1 (January 2014) - Kouvelas, Anastasios; Lioris, Jennie; Fayazi, S. Alireza; Varaiya, Pravin
In this paper the problem of arterial signal control is considered. Urban intersections face serious congestion problems, but the installation and maintenance of centralized systems is deemed cumbersome. A decentralized approach that is relatively simple to implement is studied. The recently proposed maximum pressure controller, demonstrated to stabilize queues in arterial traffic systems, is tested in simulations. Modifications of the controller are analyzed and compared under the same demand scenarios. The mesoscopic model used for the simulation experiments is an extended version of the store-and-forward model and emulates the arterial traffic network as a queuing system. The results demonstrate the efficiency of the maximum pressure algorithm, which, under certain conditions, can stabilize all queues in the system.